Line Spread Test Results for Commercially Available the White Rice Porridge with Sticky Barley (Global Journal of Medical Research, 2023)
In the event of a disaster we will have to take stockpiled food Retort porridge contains water and can be eaten directly from the container However there is a risk of aspiration for people with impaired swallowing function As a result of the line spread test LST which was performed after homogenizing white rice porridge with sticky barley using a mixer it was found that the viscosity was weak and there was a risk of aspiration for people with weakened swallowing function The thickness was added to white rice porridge with sticky barley by using four types of commercially available thickening agents that was made into a uniform liquid with a mixer A line spread test LST was performed by adding 2 g of each thickening agent to 100g of liquid porridge As a result the viscosity of the liquid porridge was stabilized and thickened and it became a state that could swallow more safely In the line spread test the thickness of the porridge was measured after 30 seconds 5 minutes 15 minutes and 30 minutes
Keywords: commercial product; white rice porridge with sticky barley; lin spread test (LST); thickener